2013
DOI: 10.1172/jci65842
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial vitamin D receptor signaling inhibits experimental colitis

Abstract: The inhibitory effects of vitamin D on colitis have been previously documented. Global vitamin D receptor (VDR) deletion exaggerates colitis, but the relative anticolitic contribution of epithelial and nonepithelial VDR signaling is unknown. Here, we showed that colonic epithelial VDR expression was substantially reduced in patients with Crohn's disease or ulcerative colitis. Moreover, targeted expression of human VDR (hVDR) in intestinal epithelial cells (IECs) protected mice from developing colitis. In exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
286
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(317 citation statements)
references
References 78 publications
23
286
1
2
Order By: Relevance
“…Taken together with our results demonstrating the association between serum 25(OH)D concentrations and disease activity, these conclusions support data from in vitro cell culture studies and in vivo animal models that the vitamin D-VDR axis exerts dual roles in protecting against colitis by maintaining epithelial barrier function and decreasing mucosal inflammation (22,23 gene transcription and stabilizing the VDR protein (45)(46)(47). Previous work has demonstrated that the VDR-retinoid X receptor heterodimer binds at the VDR gene itself, and VDR transcripts have been reported to increase with vitamin D 3 treatment in lymphoblastoid cells (48).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Taken together with our results demonstrating the association between serum 25(OH)D concentrations and disease activity, these conclusions support data from in vitro cell culture studies and in vivo animal models that the vitamin D-VDR axis exerts dual roles in protecting against colitis by maintaining epithelial barrier function and decreasing mucosal inflammation (22,23 gene transcription and stabilizing the VDR protein (45)(46)(47). Previous work has demonstrated that the VDR-retinoid X receptor heterodimer binds at the VDR gene itself, and VDR transcripts have been reported to increase with vitamin D 3 treatment in lymphoblastoid cells (48).…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, our group has demonstrated that, as a protective mechanism against mucosal inflammation, vitamin D signaling inhibits gut epithelial cell apoptosis by downregulating nuclear transcription factor kB (NF-kB), which in turn downregulates the p53 modulator of apoptosis, a key positive regulator of gut epithelial cell apoptosis (23). As such, we hypothesize that this inhibition of apoptosis contributes to preserving epithelial tight junction proteins.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Having identified the essential role of EZH2 in DSS-induced colitis, we used another disease model to substantiate this idea. The 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis model acts via acute destruction of the intestinal barrier and involves Th1-mediated mucosal inflammation, thereby mimicking CD in humans (27,28). We challenged wild-type and EZH2 IEC−/− mice with TNBS to assess the role of epithelial EZH2 in this model.…”
Section: Notably the Hyperinfiltration Of Immune Cells In The Ezh2mentioning
confidence: 99%
“…For instance, vitamin D deficiency, which is common among coeliac [17,18] and asthmatic patients [19,20], seems to have unfavourable effects on immune regulation [21], gut microbial balance and the intestinal mucosal barrier [22][23][24]. Therefore, vitamin D deficiency may be a common factor capable of increasing the risk of developing both coeliac disease and asthma.…”
Section: Discussionmentioning
confidence: 99%